2018 13th IEEE International Conference on Automatic Face &Amp; Gesture Recognition (FG 2018) 2018
DOI: 10.1109/fg.2018.00022
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Facial Photo-Sketch Synthesis Using Multi-Adversarial Networks

Abstract: Synthesizing face sketches from real photos and its inverse have many applications. However, photo/sketch synthesis remains a challenging problem due to the fact that photo and sketch have different characteristics. In this work, we consider this task as an image-to-image translation problem and explore the recently popular generative models (GANs) to generate high-quality realistic photos from sketches and sketches from photos. Recent GANbased methods have shown promising results on image-toimage translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 49 publications
0
93
0
Order By: Relevance
“…Though we have only evaluated our approach on polarimetric thermal to visible face verification, in the future, we will evaluate the performance of this method on other heterogeneous face recognition tasks such as sketch to face matching [32].…”
Section: Resultsmentioning
confidence: 99%
“…Though we have only evaluated our approach on polarimetric thermal to visible face verification, in the future, we will evaluate the performance of this method on other heterogeneous face recognition tasks such as sketch to face matching [32].…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the effectiveness of our model, we compare our results both qualitatively and quantitatively with seven other methods, namely MWF [3], SSD [1], RSLCR [13], DGFL [4], FCN [14], Pix2Pix-GAN [28], and Cycle-GAN [7]. We also compare our results quantitatively with the latest GAN based sketch synthesis methods, i.e., PS 2 -MAN [29] and stack-CA-GAN [18]. Since the models of their work are not available, we can only compare with the results that are directly taken from their published papers.…”
Section: Evaluation On Public Benchmarksmentioning
confidence: 95%
“…Image Quality Assessment For datasets with ground truth sketches (e.g., CUFS and CUFSF), previous work [13,18,4] typically used structural similarity (SSIM) [31] as an image quality assessment metric to measure the similarity between a generated sketch and the ground truth sketch. However, many researchers (e.g., in super resolution [32] and face sketch synthesis [30,29]) pointed out that SSIM is not always consistent with the perceptual quality. One main reason is that SSIM favors slightly blurry images when the images contain rich textures.…”
Section: Quantitative Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works such as [14,15,16,17] have demonstrated that different sized objects are captured by different layers in a deep network. Hence, an obvious approach would be to design a multi-scale counting network [18,19] that concatenates feature maps from different layers of the VGG16 network. However, earlier layers in a deep network capture primitive features and do not learn semantic awareness.…”
Section: Introductionmentioning
confidence: 99%